Standardization of Orthoshiphon stamineus raw material and extracts for anti-uterine fibroid - Mohd, K.S.; Halim, N.H.; Pauzi, N.; Hamil, S.H.R.; Shafaei, A.; Ismail, Z. (2017)
This study aim to evaluate gravimetric parameters and physicochemical of raw materials of Orthosiphon stamineus in order to ascertain the quality of plant materials and achieved standardized material. Anti-uterine fibroid potential was investigated by cytotoxicity test on uterine leiomyosarcoma cell SK-UT-1. Gravimetric analysis showed that all parameters adhered to the standard according to Malaysian Herbal Monograph. Primary and secondary metabolites screening revealed that aqueous extract have highest total glycosaponins, total phenolics and total phospholipids with the amounts of 27.38%, 18.75% and 3.17%, respectively. Meanwhile, 50% ethanolic extract have highest total proteins, total polysaccharides and total flavonoid with amounts of 9.2%, 19.79%, 8.13%, respectively. Evaluation of cytotoxic potency showed that aqueous extract was more cytotoxic compared to 50% ethanolic extract with the IC50 18µg/mL and 34µg/mL, respectively. Mode of cell death analysis by AO/PI double staining substantiated apoptosis induction by water extract. The results of this study can serve as reference data for standardization of O. stamineus extracts for development as anti-uterine fibroid.